X (3872) as a molecular DD* state in a potential model; Physical Review D; Vol. 60, iss. 9 - Ian Woo Lee; Faessler A.; Gutsche Th.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2009, 2009)
Title screen